Pengaruh Waktu Inokulasi Inokulum Dalam Pembuatan Bioetanol Dari Pelepah Sawit Menggunakan Saccharomyces cerevisiae - Siburian, Roy Ronald; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Palm frond is one of the solid waste generated by the activities of oil palm plantations. Indonesia is one of the countries which has the wide land areas in the world. Palm frond is lignocellulosic compound that consist of lignin, celluose, and hemicelluloce. Therefore, palm fronds can be used as raw material to produce bioethanol, production of bioethanol from palm fronds can be done through the fermentation process. The microorganisms that used in this research was Saccharomyces cerevisiae. The purpose of this research was to determine the effect of inoculation time of Saccharomyces cerevisiae on fermentation process to produce bioethanol from palm fronds. Stages of the process that done in this research include delignification, purification powder palm frond, hydrolysis and fermentation. In the fermentation process, the inoculation inoculum's time varied for 12 hours, 24 hours, 36 hours and 48 hours. On acid hydrolysis, the result of sugar concentration maximum was 54.889 g/L. The optimum time of inoculum inoculation in this research was 24 hours and the optimum bioethanol gained from fermentation proces was 3% (v/v) for 3 days.Keywords : bioethanol, fermentation, hydrolysis, inoculum, palm frond, Saccharomyces cerevisiae